Scheme of periodization of faulting stages in the Earth's crust of the Ukrainian shield - new data - Gintov, O.B. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2014)
On the basis of petrological study and reference isotopic geochronological age determinations of Precambrian rocks of the Ukrainian shield (USh), published lately, a refined geochronological scale of stages of deformation (faulting) of the Earth's crust in this region has been made up. It is shown that the suture zones of the USh - Golovanevsk, Ingulets-Krivoy Rog and Orekhov-Pavlograd - were simultaneously formed in the Early Proterozoic. These data allowed us to clarify the scheme and the mechanism of geodynamic evolution of the central and eastern parts of the shield in the Early Precambrian. Plate tectonic mechanism of formation of the lithosphere structure of this part of the USh was provided with the action of two convection cells (or plumes) - regional and pulsating local ones.